Discovering meta-models of low-code applications - Moreira, Fernando Gabriel Ferreira (2022)
Low-code platforms (LCAP) enable users to create apps of various types quickly and with little or no coding in general purpose programming languages. Despite their popularity, these platforms are often closed source and do not adhere to standards. Users of these platforms face two major issues: the first is the difficulty in the evolution of applications in terms of platform updates, and the second is the inability to migrate the applications to another platform, constraining the user into using the original platform. Thus, the goal of this work is to investigate the feasibility of discovering these platforms’ meta-models using models exported by them as a starting point. This will enable apps to be migrated, for example, to a new version of the platform or to a different platform by describing transformations using the discovered meta-models.